Different profiles of acute graft pyelonephritis among kidney recipients from standard or elderly donors - Tarragoni, Rita; Congiu, Giovanni; Mella, Alberto; Augelli, Giovanni; Fop, Fabrizio; Dolla, Caterina; Gallo, Ester; Di Vico, Maria Cristina; Faletti, Riccardo; Bosio, Andrea; Gontero, Paolo; Costa, Cristina; et al. (Frontiers in Medicine, 2024)
Background. Acute graft pyelonephritis (AGPN) is a relatively common complication in kidney transplants (KTs); however, the effects on allograft function, diagnostic criteria, and risk factors are not well established.Retrospective analysis of all consecutive adult kidney transplants (KTs) performed between 01/01/2011-12/31/2018 (follow-up ended on 12/31/2019) to examine the association between the diagnosis of AGPN (confirmed with Magnetic Resonance Imaging [MRI]) during the first post-transplantation year and graft outcomes.Results. Among the 939 consecutive KTs (≈50% with donors≥60 years), we identified 130 MRIconfirmed AGPN episodes, with a documented association with recurrent and multidrug-resistant bacteria UTIs (p<0.005). Ureteral stenosis was the only risk factor associated with AGPN (OR 2.9 [95% CI, 1.6 to 5.2]). KTs with AGPN had a decreased allograft function at one year (ΔeGFR 6 ml/min/1.73 m 2 [-2-15] in non-AGPN vs. -0.2 [-6.5-8.5] in AGPN, p<0.001), with similar and negative profiles in KTs from standard or elderly donors. However, only KTs with AGPN and a donor<60 years showed reduced death-censored graft survival (p=0.015); most of this subgroup received anti-thymocyte globulin (ATG) induction (40.4% vs. 17.7%), and their MRI presented either a multifocal AGPN pattern (73.9% vs. 56.7%) or abscedation (28.3% vs. 11.7%). No difference was noted in death-censored graft survival between early (< 3 months post-KT) or late (3-12 months) AGPN, solitary/recurrent forms, or types of multidrug-resistant pathogens. Linear regression confirmed the independent role of multifocal pattern, abscedation, ATG induction, and donor age on the eGFR at one year.AGPN, influenced by multifocal presentation, ATG induction, donor age, and abscessualization, affects kidney function and significantly impacts allograft survival in KTs with donors<60 years.